2015
DOI: 10.1292/jvms.15-0213
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> host range of feline morbillivirus

Abstract: Feline morbillivirus (FmoPV) is an emerging virus in cats, which is associated with tubulointerstitial nephritis. To study the in vitro host range of FmoPV, we inoculated FmoPV strain SS1 to 32 cell lines originated from 13 species and cultured for 2 weeks, followed by RNA extraction and reverse-transcription-polymerase chain reaction for FmoPV detection. As a result, only cell lines derived from cats and African green monkeys were susceptible to FmoPV. FmoPV infects diverse feline cell lines: epithelial, fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
2
27
0
Order By: Relevance
“…The presence of FeMV in the liver of infected cats, most of which were affected by cholangiohepatitis, was already demonstrated through immunohistochemistry (Yilmaz et al, 2017). Moreover, studies in vitro demonstrated that FeMV may have tropism for several cellular lines therefore being potentially able to infect different organs (Sakaguchi et al, 2015). The cat with FeMV-positive urine had no medical requirements to perform a kidney biopsy.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of FeMV in the liver of infected cats, most of which were affected by cholangiohepatitis, was already demonstrated through immunohistochemistry (Yilmaz et al, 2017). Moreover, studies in vitro demonstrated that FeMV may have tropism for several cellular lines therefore being potentially able to infect different organs (Sakaguchi et al, 2015). The cat with FeMV-positive urine had no medical requirements to perform a kidney biopsy.…”
Section: Discussionmentioning
confidence: 97%
“…Table 1 Molecular prevalence of FeMV sequences in cat urine or kidney tissues in published studies Table 2 Seroprevalence A single study evaluating FeMV cell tropism in vitro documented viral replication in cat fibroblasts, lymphoid cells and glial cells. 43 No other morbilliviruses have been linked to kidney disease (see box on page 8), although they can infect epithelial cells of the urogenital tract. in addition to the hypothesis that FeMV may cause kidney disease, one study has suggested a potential association with liver disease, 28 although strong evidence is lacking.…”
Section: Pathogenesismentioning
confidence: 99%
“…57,58 o Morbillivirus: Several studies have raised interest in a potential association between CKD and morbillivirus infection (FmoPV), a paramyxovirus identified in cats. [59][60][61][62][63] The virus was shown to have cytopathic effects in FCRK cell lines and in small numbers of stray cats there seemed to be a higher prevalence of tubulointerstitial nephritis in the cats that were positive for the feline morbillivirus than in negative cats, although little demographic and phenotypic data was available for either group. 62 FmoPV has also been identified in the urine (10%) and blood (6%) of stray cats in a study performed in Japan, and at a higher prevalence from renal tissue (40%; 4/10) from cats with CKD.…”
Section: Association Of the Development Of Chronic Kidney Disease Witmentioning
confidence: 99%